Colonic Basidiobolomycosis—An Unusual Presentation of Eosinophilic Intestinal Inflammation - Kurteva, Elena; Bamford, Alasdair; Cross, Kate; Watson, Tom; Owens, Catherine; Cheng, Fanlek; Hartley, John; Harris, Kathryn; Johnson, Elizabeth M.; Lindley, Keith; Levine, Samantha; Köglmeier, Jutta (Frontiers in Pediatrics, 2020)
Basidiobolomycosis is a rare fungal disease caused by Basidiobolus ranarum. Involvement of the gastrointestinal tract is unusual and poses both a diagnostic and therapeutic challenge, as clinical signs are nonspecific and predisposing risk factors are lacking. It can mimick inflammatory bowel disease, primary immunodeficiency or a malignancy and should be considered in patients who do not respond to standard therapy. We present the case of a twenty two month old boy with confirmed colonic Basidiobolomycosis, who presented with severe eosinophilic inflammation of the gastrointestinal tract. Panfungal PCR performed on DNA extracted directly from a tissue sample confirmed the presence of Basidiobolus. He made a full recovery with a combination of surgery and prolonged targeted antifungal medication.